Leveraging green HRM for firm performance: The joint effects of CEO environmental belief and external pollution severity and the mediating role of employee environmental commitment - Ren, Shuang; Jiang, Kaifeng; Tang, Guiyao (Human Resource Management, 2022)
AbstractThe topic of green human resource management (HRM) has drawn increasing attention of HRM scholars in the past decade. Recent research has called for more studies to identify the antecedents of green HRM used in organizations and explore the mediating mechanisms through which green HRM is related to performance outcomes. This study represents an effort to address these research needs by examining the joint effects of chief executive officer (CEO) environmental belief and external pollution severity on the use of green HRM and testing the mediating role of employee environmental commitment in the relationship between green HRM and firm performance. Drawing upon data collected from multiple sources (i.e., survey data from chief executive officer (CEOs), chief financial officers (CFOs), HR managers and employees, and archival data from government statistics), we found that CEO's environmental belief is significantly related to the use of green HRM, especially for companies operating in locations with severer pollution. Green HRM in turn has a positive relationship with the firm's environmental and financial performances via employee commitment to the environment. The findings highlight the often‐overlooked role of in the strategic HRM literature pertinent to environmental management and clarify the antecedents and influential mechanisms of green HRM at the firm level of analysis. We also discuss theoretical and practical implications in this study.